Does Governance Cause Growth? Evidence from China - Ross Wilson (Lund University, School of Economics and Management, Department of Economics, 2015)
This study uses heterogeneous panel Granger causality tests to investigate the causal relationships between quality of governance and economic growth at the provincial level in China during the reform era. I find a significant and positive effect of economic growth on subsequent quality of governance, largely driven by growth in the secondary sector, but no significant effect of quality of governance on economic growth. These findings suggest that improvements in formal governance have not been a key factor in China's rapid growth, and support the proposition that governance reforms are often a consequence, rather than a cause, of economic growth.
Keywords: O11; O17; O43; O53; R11; 330; Asia; China; Quality of Governance; Economic Growth